Cellphones linked to brain tumors. - Predd, P.P (IEEE spectrum)
Millions of research dollars have been spent worldwide to determine whether cellphones cause brain tumors. Now, what health experts call a large-scale, well-conducted study has yielded the most conclusive evidence of such a link to date. Researchers have found an association between long-term cellphone use and a rare, benign tumor, causing concern among radiation specialists and epidemiologists, though they emphasize that the results haven't been replicated yet. It found that people who used cellphones for more than 10 years doubled their risk of developing the tumor, a benign condition affecting one in 100 000 people. Acoustic neuroma grows on the nerve connecting the brain and the inner ear, causing hearing loss. The risk was four times as high on the side of the head where the phone was usually held. Thirteen countries, the United States not among them, are a part of this collaborative effort coordinated by the International Agency for Research on Cancer. The first research paper showed no link between acoustic neuroma and cellphone use, but it contained fewer subjects with long-term exposure. If cellphone users want to be cautious, Foster advises, they can reduce the hours they spend calling on the go or use headsets. Forget about RF-shielding and radiation-reduction devices, says Foster. According to him, they don't work.